2021
DOI: 10.1111/opn.12362
|View full text |Cite
|
Sign up to set email alerts
|

Older patients’ perspectives and experience of hospitalisation during the COVID‐19 pandemic: a qualitative explorative study

Abstract: Background and Objectives The aim of this study was to gain in‐depth knowledge and an increased understanding on how isolation from close relatives and carers, during the COVID‐19 pandemic, impacted older patients during hospitalisation in a Geriatric department. Method We conducted a qualitative study using semi‐structured interviews and a phenomenological‐hermeneutic approach, to get an understanding of the older participants' perspectives and lived experiences. Compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 32 publications
(45 reference statements)
1
44
0
3
Order By: Relevance
“…Patients Eight (11.6%) of the included studies addressed loss and grief among the general patient population, highlighting patients' loss of physical health and the attendant emotional responses. [2][3][4][5][6][7][8][9] Initial symptoms such as fever, cough, anosmia and dysgeusia gave rise to anxiety and fear while social isolation resulted in boredom and loneliness. [2][3][4][5][6][7][8][9] Anxiety revolved around the family's well-being and the risk of transmitting the infection to them.…”
Section: Discussionmentioning
confidence: 99%
“…Patients Eight (11.6%) of the included studies addressed loss and grief among the general patient population, highlighting patients' loss of physical health and the attendant emotional responses. [2][3][4][5][6][7][8][9] Initial symptoms such as fever, cough, anosmia and dysgeusia gave rise to anxiety and fear while social isolation resulted in boredom and loneliness. [2][3][4][5][6][7][8][9] Anxiety revolved around the family's well-being and the risk of transmitting the infection to them.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of concern as older people living alone is a growing group in many countries, particular in Europe where more than 30% of all persons 65 + live alone [ 27 ]. The Covid-19 pandemic has also painfully exposed the vulnerability of this group of older persons.’ [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…15, 16 Moreover, a qualitative study from Denmark found that older patients experienced anxiety and a loss of dignity and autonomy during hospitalisation. 17…”
Section: Previous Researchmentioning
confidence: 99%
“…15,16 Moreover, a qualitative study from Denmark found that older patients experienced anxiety and a loss of dignity and autonomy during hospitalisation. 17 Research also shows that access to and delivery of healthcare were challenged during the pandemic, especially related to the access to ventilators 18 Both high income and low-income countries experienced barriers to COVID-19 testing. 19,20 In Norway, health trusts were forced to change routines daily in response to the unpredictable situation and to mitigate the expected rapid increase in numbers of infections and COVID-19 patients.…”
Section: Previous Researchmentioning
confidence: 99%